Memnon, the Strategist - Sarakinski, Vojislav; Panovski, Stefan (Филозофски факултет, Скопје, 2011)
The general impression on Memnon of Rhodes that is transmitted by our sources – and is more or less unanimously accepted in modern historiography – is that he may have been the only military commander able to bring the relentless Alexander III to a halt and disrupt his plans. This opinion seems to be based on Memnon’s few successes, which could purportedly imperil the Asian expedition of Alexander: namely, Memnon’s achievements against Parmenio; his sensible proposal to avoid direct altercation with the Macedonians; the gallant defence of Halicarnassus; and particularly, his dangerous naval campaign in the Aegean Sea in 333 BC. In this paper, we will consider whether Memnon’s actions, as well as their results, truly validate the impression and reputation he has acquired both in antiquity and today.